The Principles of Good Judiciary in Indonesia and Malaysia - Sudrajat, Tedi (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4438, 2021)
The judiciary is part of the government, so it is obliged to implement good governance in judicial administration. the principles of good judiciary at least contain elements of equal treatment by the law (equality before the law), honesty (fairness), impartiality, freedom in making verdict, the ability (competency), the open integrity or transparency, easy to visit (easy access), timely (timeliness), certainty. Indonesia and Malaysia have accommodated the principles of good judiciary, such as: the principle of judicial independence, the principle of legality, the principle of impartiality, the principle of judgment must be accompanied by reasons, the principle of easy access, the principle of audi et alteram partem , and the principle of openness to trials. The mechanism for implementing good judgment in these two countries is carried out by accommodating these principles in statutory regulations